THE EFFECT OF FISCAL DECENTRALIZATION, CAPITAL EXPENDITURE, TOTAL POPULATION, AND AVERAGE LENGTH OF SCHOOL TO THE GDP GROWTH OF WEST SULAWESI PROVINCE 2006 ̶ 2013 - Hilmy Hilmy (Badan Penelitian dan Pengembangan Daerah Provinsi Sulawesi Barat, 2020)
The empirical studies that have been done show that fiscal decentralization can bring a positive or negative impact as well as some research to get the result that there is no relationship between fiscal decentralization on economic growth. Fiscal decentralization role in stimulating economic growth has been a concern of many countries, include in Indonesia. Since 2001, effectively the Indonesian government has run large fiscal decentralization policy as a strategy to accelerate regional development. This study aims to examine the effect of fiscal decentralization on GRDP growth in West Sulawesi Province. The standard of the fiscal decentralization used in the analysis is expenditure indicator. The impact of the fiscal decentralization on GRDP growth will be viewed together with other variables that are have function as determinant factors to economic growth, in this case it called the control variables, such as; population, capital expenditure, and the accumulation of human capital represented by average length of school. The autor use data panel from 5 distrcts in West Sulawesi Province which cover the years period (2006 – 2013). Analysis performed by multiple regression analysis model by using fixed effect estimation model. The analysis show that indicators of fiscal desentralization does not have significant impact on GRDP growth in West Sulawesi Province. The Capital Expenditure variable, population and average length of school have positive and significant impact on GRDP growth districts in West Sulawesi Province.